The Effectiveness of Teachers’ Use of Lecture Model Combined with Cooperative Learning Method for Enhancing Students’ Problem-Solving Skills in Physics - Rahmi Putri Z; Jumadi Jumadi; Ariswan Ariswan; Ratnasari Ratnasari; Depi Oktasari (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2019)
This study investigates the effect of the use of teachers’ Lecture models combined with cooperative learning methods to improve students’ problem-solving skills in physics compare with the control group who were not exposed to the lecture model combined with cooperative learning methods from effect size value. The research method was a quasi-experimental research. The sample consisted of 33 students of 10th grade in middle schools (senior high school), SMAN 1 Sungai Penuh, Jambi Province where they ware learn at work and energy concept. Students' achievements, as well as their problem-solving skills of work and energy concept were assessed by pretest-posttest with an essay test. The results showed that the experimental group’s learning process has a high effect size value to problem-solving skills more than control group learning process. That shows the lecture model combined with cooperative learning method more effective than lecture model.